Essential life-saving skills for schoolchildren: a scoping review - Jamaludin, Thandar Soe @ Sumaiyah; Nurumal, Mohd. Said; Sanusi, Zainal Abidin; Che Hasan, Muhammad Kamil; Firdaus, Mohd Khairul Zul Hasymi; Che Abdullah, Che Azunie; Win, Kyu Kyu; Sutrisno, Resti Yulianti (IIUM Press, 2024)
Background: Teaching lifesaving skills such as first aid and initial cardiopulmonary resuscitation (CPR) to schoolchildren can increase the lifelong ability and motivation of young people to take action in an emergency. Methods: This scoping review aimed to look for the literature related to the essential life-saving skills for schoolchildren, focusing on first aid and initial cardiopulmonary resuscitation (CPR) before the arrival of medical professionals. A scoping review was conducted by using the PRISMA guidelines to meet the objective of this study. Results: Fourteen articles published between 2017 and 2024 were analyzed, revealing three main themes: educational approaches for teaching first aid and CPR to schoolchildren, the effectiveness of first aid and CPR Training Programmes for schoolchildren, and barriers and facilitators of First Aid and CPR Training Programmes for schoolchildren. Conclusion: Findings suggest a crucial need to equip schoolchildren with the necessary skills to respond effectively to emergencies. Recommendations include implementing comprehensive first aid and CPR training programmes as life-saving skills for schoolchildren in schools